Recovery From Rheumatoid Arthritis Following 15 Months of Therapy With Low Doses of Ionizing Radiation: A Case Report - Shuji Kojima; Mitsutoshi Thukimoto; Jerry M. Cuttler; Kiyomi Inoguchi; Takahiro Ootaki; Noriko Shimura; Hironobu Koga; Akihisa Murata (SAGE Publishing, 2018)
Rheumatoid arthritis (RA) is an inflammatory autoimmune disease that occurs commonly in old people. Hot spring radon therapy is widely practiced in Central Europe and Japan for relief from the painful symptoms. The usual duration of a spa treatment is a week or two, and the relief is temporary. This article reports on the near-complete recovery of a patient who had been suffering from RA for 10 years. The patient received 15 months of low-dose radon and γ-radiation therapy in a room that reproduced the conditions of a radon spa. The daily 40-minute exposure in the therapy room was supplemented by ten 6-minute radio-nebulizer treatments. The inflammation markers C-reactive protein and matrix metalloproteinase 3 declined strongly to the normal level of 0.07 mg/dL and the near-normal level of 48.9 ng/mL, respectively. After the patient's return to good health, the frequency of the visits was reduced to twice each month. The patient's protection systems appear to have adapted to stimulated conditions, sufficiently to sustain the recovery from RA. Such a long-term course of treatments and follow-up maintenance could be carried out in any hospital that has these low-dose radiation therapy rooms. The therapy could be scheduled to suit patient availability.